2009
DOI: 10.3109/07357900902744486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naturally Occurring Polymethyoxyflavonoids on Cell Growth, P-Glycoprotein Function, Cell Cycle, and Apoptosis of Daunorubicin-Resistant T Lymphoblastoid Leukemia Cells

Abstract: Effects of polymethoxyflavonoids tangeretin and nobiletin and the related polyphenolic compounds baicalein, wogonin, quercetin, and epigallocatechin gallate on the cell growth, P-glycoprotein function, apoptosis, and cell cycle of human T lymphoblastoid leukemia MOLT-4 and its daunorubicin-resistant cells were investigated. The IC50 values of these compounds on the cell growth were 7.1-32.2 micromol/L, and the inhibitory effects were observed to be almost equal to the parent MOLT-4 and the daunorubicin-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
5
42
1
Order By: Relevance
“…Besides the involvement of altered redox status in apoptosis induction triggered by these compounds, anti-inflammatory effects, antiangiogenesis, anti-invasiveness and induction of differentiation are well known to be implicated in their broad biological functions. It is worthy of note that flavonoids have been revealed to inhibit the function of ATP-binding cassette transporters such as multidrug resistance-associated proteins as well as P-glycoprotein [90], similar to our recent study [91]. On the other hand, a recent study demonstrated that berry anthocyanins, such as cyanidin-3-galactosidee, and cyanidin-3-glucoside as well as peonidin-3-glucosid, exhibit affinities for the efflux transporters breast cancer resistance protein (BCRP) and consequently may be actively transported out of intestinal tissues and endothelia [92].…”
Section: Resultssupporting
confidence: 63%
“…Besides the involvement of altered redox status in apoptosis induction triggered by these compounds, anti-inflammatory effects, antiangiogenesis, anti-invasiveness and induction of differentiation are well known to be implicated in their broad biological functions. It is worthy of note that flavonoids have been revealed to inhibit the function of ATP-binding cassette transporters such as multidrug resistance-associated proteins as well as P-glycoprotein [90], similar to our recent study [91]. On the other hand, a recent study demonstrated that berry anthocyanins, such as cyanidin-3-galactosidee, and cyanidin-3-glucoside as well as peonidin-3-glucosid, exhibit affinities for the efflux transporters breast cancer resistance protein (BCRP) and consequently may be actively transported out of intestinal tissues and endothelia [92].…”
Section: Resultssupporting
confidence: 63%
“…8 In addition, the inhibitory potency of wogonin was nearly equal to that of the first-generation P-glycoprotein inhibitor, 3 verapamil. 8 We had taken the lead to investigate the influence of wogonin, and the results show that it did downregulate transcription of MDR1 mRNA and expression of P-glycoprotein in K562/A02 cells.…”
Section: Discussionmentioning
confidence: 91%
“…One study has shown that wogonin 10-30 µmol/L acted as an inhibitor of P-glycoprotein and consequently increased the cellular content of chemotherapeutic agents in multidrug resistant cancer cells. 8 On the other hand, wogonin can inhibit apoptosis induced by chemotherapeutic agents in normal cells, such as thymocytes. 9 However, sequential or concurrent administration of a chemosensitizer and a cytotoxic drug or a combination of drugs cannot guarantee the co-action of intended drugs in the same cancer cells because of their different pharmacokinetics and tissue disposition.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described various biological effects of nobiletin like anti-inflammatory, anti-tumor, anti-metas -tasis and neuroprotective properties (Murakami et al, 2000;Nakajima et al, 2007;Li et al, 2006;Shi et al, 2013). Recent studies have also demonstrated compelling role of nobiletin in initiating anti-cancerous proper -ties in various cell culture systems (Luo et al, 2009;Ishii et al, 2010). In order to observe any effect of nobiletin on bone cancer cells, MTT and LDH assay was performed (Figure 2).…”
mentioning
confidence: 99%
“…Regulation of cell cycle checkpoint also eliminates impaired cells either by inducing apoptosis or blocking cell cycle progression (causing apoptosis). Nobiletin has been demonstrated to possess anti-proliferative properties by promoting apoptosis and cell cycle arrest (Luo et al, 2008, Luo et al, 2009Ishii et al, 2010). Thus, to confirm the effect of nobiletin on apoptosis and cell proliferation of SaOS-2 cells flow cytometry was performed.…”
mentioning
confidence: 99%